2023
DOI: 10.1155/2023/8072369
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Hub Genes and Immune Cells Associated with the Formation of Acute Aortic Dissection

Abstract: Background. Acute type A aortic dissection (AAD) is a catastrophic disease with high mortality, but the pathogenesis has not been fully elucidated. This study is aimed at identifying hub genes and immune cells associated with the pathogenesis of AAD. Methods. The datasets were downloaded from Gene Expression Omnibus (GEO). Gene Set Enrichment Analysis (GSEA), gene set variation analysis (GSVA), and differential analysis were performed. The differentially expressed genes (DEGs) were intersected with specific ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…In our results in TAO (a vascular disease that involves medium and small vessels without atherosclerosis and causes narrowing and occlusions as a result of the inflammation of arteries and veins) patients, we detected an increase in RNF149 expression. Zhong et al found that EIF4A1 expression was upregulated in the aortic wall tissues of patients with acute type A aortic dissection, a catastrophic disease with high mortality but whose pathogenesis is not fully elucidated [63]. Similarly, we found that EIF4A1 expression was upregulated in TAO disease with fine arterial occlusions.…”
Section: Discussionsupporting
confidence: 70%
“…In our results in TAO (a vascular disease that involves medium and small vessels without atherosclerosis and causes narrowing and occlusions as a result of the inflammation of arteries and veins) patients, we detected an increase in RNF149 expression. Zhong et al found that EIF4A1 expression was upregulated in the aortic wall tissues of patients with acute type A aortic dissection, a catastrophic disease with high mortality but whose pathogenesis is not fully elucidated [63]. Similarly, we found that EIF4A1 expression was upregulated in TAO disease with fine arterial occlusions.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have identified hub genes in AD using bioinformatic strategies. [13][14][15][16] For example, Li et al calculated the immune scores of AD patients and identified key immune related genes by WGCNA and PPI analyses. 14 Zhong et al 16 and Luo et al 17 first identified AD associated genes via WGCNA and then calculated their correlations with immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] For example, Li et al calculated the immune scores of AD patients and identified key immune related genes by WGCNA and PPI analyses. 14 Zhong et al 16 and Luo et al 17 first identified AD associated genes via WGCNA and then calculated their correlations with immune cells. In addition, Zeng et al 18 and Ren et al 19 performed mass spectrometry to identify biomarkers in the serum of AD patients via differential expression and correlation analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Then, R software version 3.2 was applied to calculate the related coefficient between different immune-cells in the enrolled sample data and visualize the results, so as to analyze the differences between the RA and the control group as well as the correlation between each immune cell. Additionally, R software was used to conduct and visualize the correlation betwixt hub genes and immune infiltration [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%